Fiware: A web of things development platform - Tot, Ivan A.; Bogićević, Dušan Lj.; Trikoš, Mladen B.; Lalović, Komlen G. (Vojnotehnički glasnik / Military Technical Courier, 2018)
As an extension to the concept of the Internet of Things (IoT), Web of Things (WoT) represents a step towards connecting smart things to the existing web environment while considering issues such as heterogeneity, scalability, and usability. This paper is dedicated to current opportunities as well as challenges for development in the concept of WoT. The theoretical foundations of the Internet of Things concept, such as architecture, protocols, services, and things themselves, which form the basis of both concepts, are described in the paper. The paper deals with the necessary preconditions for developing the concept of Web of Things. The main contribution of the paper is a proposal of architecture based on the FIWARE platform as the basis for the development of Web of Things.The demonstration of the proposed architecture is described by a real case scenario.